1978
DOI: 10.1136/thx.33.3.359
|View full text |Cite
|
Sign up to set email alerts
|

Intrathoracic neural tumours.

Abstract: . (1978). Thorax, 33,[359][360][361][362][363][364][365][366][367]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
3

Year Published

1983
1983
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(45 citation statements)
references
References 10 publications
1
41
0
3
Order By: Relevance
“…Our incidence of malignancy in children was 61.5%. In adults, most of the tumours are described as benign (2,4,12). In our patients, the malignancy rate in adults was 8.5%, which is similar to that of other reports (8,12).…”
Section: Follow-upsupporting
confidence: 79%
See 1 more Smart Citation
“…Our incidence of malignancy in children was 61.5%. In adults, most of the tumours are described as benign (2,4,12). In our patients, the malignancy rate in adults was 8.5%, which is similar to that of other reports (8,12).…”
Section: Follow-upsupporting
confidence: 79%
“…Approximately 90% of these tumours occur in the posterior mediastinum or paravertebral sulcus. Mediastinal neurogenic tumours are benign in most cases, with an overall incidence of malignancy ranging from 3% to 19% (1,4,5). Surgical resection is considered the primary treatment of such tumours and is usually performed through a thoracotomy (2,6).…”
Section: Ediastinal Neurogenic Tumours (Mnt) Account Formentioning
confidence: 99%
“…1 More than 90% of neurilemmoma are benign. 3 Neurilemmoma occurs with equal frequency in men and women. 2 The tumor has been reported in patients of all ages (mean age 41 years).…”
Section: Discussionmentioning
confidence: 99%
“…2 The tumor has been reported in patients of all ages (mean age 41 years). [1][2][3] Neurilemmoma may occur in any peripheral nerve and is often found in the chest wall and the posterior mediastinum. 4 Although being very rare, pulmonary neurilemmoma can occur in all respiratory tracts including the trachea, bronchus, bronchioles and alveoli.…”
Section: Discussionmentioning
confidence: 99%
“…1) Intrathoracic neurilemmoma is usually found in the posterior mediastinum and bulge from the inner surface of the bony thorax toward the thoracic cavity. 2,3) Extrathoracic neurilemmoma is extremely rare, and Sakurai, et al reported one case of extrathoracic neurilemmoma mimicking a subcutaneous tumor of the lateral chest wall. 4) To the best of our knowledge, we report the first case of dumbbellshaped neurilemmoma that had grown both outside and inside the thoracic cavity in the lateral chest wall.…”
Section: Introductionmentioning
confidence: 99%